(untitled) (Web of Teachers: Inderscience Research, 2024)
Determining the intersection of surfaces is a fundamental concept in mathematics and physics, especially in the study of three-dimensional geometry. When two surfaces intersect, they form a line where the points on both surfaces coincide. This line represents the common boundary between two surfaces and provides important information about their relationship and properties.